The Impact of Antibiotic-Mediated Modification of the Intestinal Microbiome on Outcomes of Allogeneic Hematopoietic Cell Transplantation: Systematic Review and Meta-Analysis - Maria Gavriilaki; Ioanna Sakellari; Αchilles Anagnostopoulos; Eleni Gavriilaki (2020)
Accumulating evidence points toward a protective role of intestinal microbiota diversity in allogeneic hematopoietic cell transplantation (allo-HCT). The purpose of this systematic review and meta-analysis is to determine the effect of antibiotic-mediated disruption of microbiota on main allo-HCT outcomes (graft-versus-host disease [GVHD], treatment-related mortality [TRM], overall survival [OS]). Following literature search, 2 reviewers screened eligible studies and assessed risk of bias (RoB). Meta-analysis was performed using Review Manager Software. Among 443 screened references, 18 were eligible for meta-analysis. In studies with genomic markers, grade II to IV acute GVHD was significantly reduced in patients not receiving gut decontamination (GD) (odds ratio [OR], 1.56; 95% confidence interval [CI], 1.20 to 2.04). In subgroup analysis, prophylaxis with systemic antibiotics conferred an increased risk of acute GVHD (OR, 1.65; 95% CI, 1.08 to 2.53). When we incorporated RoB, we found a positive correlation of intestinal GVHD with GD (OR, 1.77; 95% CI, 1.29 to 2.44). Patients with higher microbiota diversity presented increased OS (risk ratio [RR], 1.58; 95% CI, 1.19 to 2.09) and lower TRM (RR, 0.45; 95% CI, 0.26 to 0.76). Our findings confirm that GD and prophylaxis with systemic antibiotics increase acute and intestinal GVHD. Importantly, our meta-analysis was the first to show a significant effect of microbiota diversity on TRM and OS.